Analysis of requirements for scientific articles and Brazilian legislation on rainwater harvesting systems - Drummond, Ana Sofia; Almeida, Jaqueline Costa; Domingos, Ryan Rodrigues; Nunes, Dayana Martins; Soalheiro, Lívia; Cunha, Priscila Maria; Obraczka, Marcelo; Ohnuma Jr., Alfredo Akira (Ciência e Natura, 2022)
The main aim of this study was to assess the determining factors, such as storage capacity, water quality and public policies, involved in the publication of scientific articles. It also sought to investigate the influence of Brazilian legislation on particular systems for harnessing rainfall in Brazil. The methodology entailed conductinga bibliographical research of the municipal, State and federal legislation in force in Brazil for the governance of technical standards and the scientific articles about the harvesting of rainwater. A total of 6 technical standards were analyzed, together with 56 legal referrals and 63 articles from national and international periodicals taken from the Google Cloud Platform for Education, SciELO, Science Direct and CAPES, and based on the principal keywords such as a “system for harnessing rainfall” and “rainwater harvesting systems”. The results show that the works that predominated were studies on the qualitative and quantitative features of rainfall and that around 80% of the publications analyzed, addressed/made use of the main legislative instruments with regard to storage, water quality and the construction and operation of systems.All the Brazilian States with the exception of three (Minas Gerais, Roraima and Pará), have at least one incentive policy for the creation or installation of catchment systems, storage and the harvesting of rainwater in the country. It can be concluded that the laws sanctioned in Brazil for rainwater are of recent origin and that they provide mechanisms for offering incentives and ensuring their enforcement in accordance with technical criteria. However, they need updating so that there can be a broader understanding of the question of how policies for the management of water operate in the country.